THE POSSIBILITY OF ACHIEVING A SAKINAH FAMILY IN MARRIAGES INVOLVING INDIVIDUALS WITH NARCISSISTIC PERSONALITY DISORDER - Rizani, Muhammad (International Journal of Multidisciplinary Reseach, 2025)
Marriage in Islam aims to achieve tranquility (sakinah), affection (mawaddah), and compassion (rahmah), as emphasized in the Qur’an, Surah Ar-Rum [30]:21. However, the realities of modern life reveal growing psychological challenges within marriages, one of which emerges when a spouse suffers from Narcissistic Personality Disorder (NPD). This disorder is characterized by an inflated sense of self-importance, a constant need for admiration, and a lack of empathy toward others. This study adopts an interdisciplinary approach combining psychology and Islamic family law through a qualitative-descriptive analysis, exploring the possibility of building a sakinah family when one partner has NPD. The findings indicate that the egocentric and empathy-deficient traits of narcissism fundamentally contradict the principles of rahmah and mawaddah, which are the spiritual essence of an Islamic household. Drawing on empirical data from the APA (2013), Campbell & Miller (2011), and Harvard Medical School (2018), individuals with NPD tend to form manipulative and unstable relationships. From an Islamic perspective, such behavior violates the command of mu‘āsyarah bil ma‘rūf as stated in Qur’an Surah An-Nisa [4]:19. Nevertheless, Islam leaves room for recovery through psychological therapy, spiritual guidance, and Islamic family counseling. The legal maxim adh-dhararu yuzāl (“harm must be eliminated”) provides the moral foundation for allowing separation when the relationship causes emotional distress and the loss of inner peace.